Star of the party : the solar system celebrates! - Carr, Jan (M. J.); Medina, Juana, 1980- (New York : Crown Books for Young Readers, 2021)
All the planets in the solar system decide to throw Sun a birthday party. Includes facts about the planets.
K-3.
O
2.9
Keywords: Planets -- Juvenile fiction; Sun -- Juvenile fiction; Birthdays -- Juvenile fiction; Parties -- Juvenile fiction; Planets -- Fiction; Sun -- Fiction; Birthdays -- Fiction; Parties -- Fiction